Competing Risk Analysis of Outcomes of Unresectable Pancreatic Cancer Patients Undergoing Definitive Radiotherapy - Chen, Yi-Lun; Tsai, Chiao-Ling; Cheng, Jason Chia-Hsien; Wang, Chun-Wei; Yang, Shih-Hung; Tien, Yu-Wen; Kuo, Sung-Hsin (Frontiers in Oncology, 2022)
Purpose: We investigated potential factors, including clinicopathological features, treatment modalities, neutrophil-lymphocyte ratio (NLR), carbohydrate antigen (CA) 19-9 level, tumor responses correlating with overall survival (OS), local progression (LP), and distant metastases (DMs), in patients with locally advanced pancreatic cancer (LAPC) who received definitive radiotherapy (RT). Methods: We retrospectively analyzed demographic characteristics; biologically effective doses (BED10, calculated with an α/β of 10) of RT; and clinical outcomes of 57 unresectable LAPC (all pancreatic adenocarcinoma) patients receiving definitive RT using modern techniques with and without systemic therapy between January-2009 and March-2019 at our institution. We used RECIST version 1.1 to evaluate the radiographical tumor response after RT. The association between prognostic factors and OS was assessed using Kaplan-Meier analysis and a Cox regression model, whereas baseline characteristics and treatment details were collected for competing risk regression of the association with LP and DM using the Fine-Gray model. Results: A median BED10 of 67.1 Gy resulted in a disease control rate of 87.7%, and the median OS was 11.8 months after a median follow-up of 32.1 months. The 1-year OS rate, cumulative incidences of LP, and DM were 49.2%, 38.5%, and 62.9%, respectively. Multivariate analyses showed that pre-RT NLR ≥3.5 (adjusted hazard ratio [HR] = 8.245, P<0.001), CA19-9 reduction rate ≥50% (adjusted HR = 0.261, P=0.005), RT without concurrent chemotherapy (adjusted HR = 5.903, P=0.004), and administration of chemotherapy after RT (adjusted HR = 0.207, P=0.03) were independent prognostic factors for OS. Positive lymph nodal metastases (adjusted subdistribution hazard ratio [sHR] = 3.712, P=0.003) and higher tumor reduction after RT (adjusted sHR = 0.922, P<0.001) were significant prognostic factors for LP, whereas BED10 ≥67.1 Gy (adjusted sHR = 0.297, P=0.002), CA19-9 reduction rate ≥50% (adjusted sHR = 0.334, P=0.023), and RT alone (adjusted sHR = 2.633, p=0.047) were significant prognostic factors for DM. Conclusion: Our results indicate that pre-RT NLR and post-RT monitoring of CA19-9 and tumor size reduction can help identify whether patients belong to the good or poor prognostic group of LAPC. The incorporation of new systemic treatments during and after a higher BED10 RT dose for LAPC patients is warranted.